Adventures from the land of stories : Queen Red Riding Hood's guide to royalty - Colfer, Chris, 1990- (Colfer, Chris, 1990- Adventures from the Land of Stories., 2017)
"Queen Red Riding Hood from the Land of Stories gives advice and makes observations on how to rule"--